Flavonoids from Lonchocarpus muehlbergianus - Magalhães Aderbal F.; Tozzi Ana M.G.A.; Magalhães Eva G.; Blanco Ivani S.; Soriano Maria-Del-Pilar C. (Anais da Academia Brasileira de Ciências, 2004)
The light petroleum extract from the roots of Lonchocarpus muehlbergianus Hassl contained nine flavonoids, including six new ones. These are 2,4-cis-2,4,5,8-tetramethoxy-(2,3:6,7)-furanoflavan; 2,4-cis-4-hydroxy-2,5,8-trimethoxy-(2,3:6,7)-furanoflavan; 2,4-cis-2-prenyloxy-4,5,8-trimethoxy-(2,3:6,7)-fu-ranoflavan; 2,4-cis-2-prenyloxy-4-hydroxy-5,8-dimethoxy-(2,3:6,7)-furanoflavan; 2',5',6'-trimethoxy-9-(1,1-dimethylallyoxy)-[2,3:3,4]-furanochalcone; 5,6-dimethoxy-(2,3:7,8)-furanoflavone, identi-fied by analysis of their spectral data (UV, IR, ¹H and 13C NMR, 2D-NMR, NOE and MS). The natural occurrence of 2,4-dioxygenated flavan derivatives is being reported for the first time. Quantitative analysis of the petrol extract, by using reversed-phase HPLC, showed that the most abundant flavonoid in the extract is 2,4-cis-2,4,5,8- tetramethoxy-(2,3:6,7)-furanoflavan.